Edukasi Literasi Artificial Intelligence (AI) Berbasis Nilai Islam untuk Penguatan Etika Berkomunikasi di Kalangan Pelajar SMK Sasmita Jaya 2 Tangerang Selatan - Siska Yuningsih; Aminah Swarnawati; Lilik Sumarni; Yukarie Ayu Wulandari; Herdi Wisman Jaya; Muhammad Gatot Hertanto Saputra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid advancement of Artificial Intelligence (AI) in education requires students not only to develop the ability to utilize technology effectively but also to understand the ethical principles governing its use. This community service program aimed to enhance AI literacy based on Islamic values in order to strengthen ethical communication among students at SMK Sasmita Jaya 2 South Tangerang. The program employed the Participatory Learning and Action (PLA) approach through an interactive workshop consisting of a needs assessment, pre-test, instructional sessions, demonstrations, discussions, hands-on AI practice, and a post-test. The participants comprised 50 students from the Computer and Network Engineering (Teknik Komputer dan Jaringan/TKJ) program. The results demonstrated a significant improvement in participants' understanding, as indicated by an increase in the average score for the Islamic digital literacy aspect from 68.80 to 84.40 (23%), the ethical communication and Islamic character aspect from 76.20 to 89.40 (17%), and the overall average score from 72.50 to 86.90 (20%). In addition to improving participants' understanding of the responsible use of AI, the program strengthened their awareness of the importance of honesty, trustworthiness (amanah), verification of information (tabayyun), and responsibility in digital communication. These findings indicate that integrating AI literacy with Islamic values is an effective approach to developing students who possess both digital competencies and strong ethical character in responding to the rapid advancement of technology.